2010
DOI: 10.1093/humrep/deq324
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive outcome after early-onset pre-eclampsia

Abstract: The majority of women with a history of early-onset pre-eclampsia achieve or wish to achieve a second pregnancy within a few years of their delivery. Nonetheless, first pregnancy early-onset pre-eclampsia appears to have a significant impact on future reproductive health and decision-making, emphasizing the importance of careful post-partum counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Details of inclusion criteria, recruitment and study protocol have been described elsewhere [16]. In brief, women were asked to participate by their consultant perinatologist after delivery and provided written informed consent prior to enrolment.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of inclusion criteria, recruitment and study protocol have been described elsewhere [16]. In brief, women were asked to participate by their consultant perinatologist after delivery and provided written informed consent prior to enrolment.…”
Section: Study Populationmentioning
confidence: 99%
“…In brief, women were asked to participate by their consultant perinatologist after delivery and provided written informed consent prior to enrolment. Between 6 and 12 months postpartum, we registered demographic, general medical, obstetric data and relevant information on family history, and collected fasting blood samples for the measurement of thrombophilia-related factors and metabolic, inflammatory and lipid markers [16,17]. Women were advised to discontinue breastfeeding and intake of any vitamin and folic acid supplements, or either of them, at least 6 weeks prior to inclusion.…”
Section: Study Populationmentioning
confidence: 99%
“…Additionally, the quality of reporting of studies and their clinical usefulness or generalisability have been suboptimal, making prediction models unsatisfactory until now 6 . Hypertensive disorders of pregnancy may have significant psychological impact on women and their partners, and many parents refrain from future pregnancies because of their earlier experiences 7–9 . Therefore, informed counselling about future pregnancies is important.…”
Section: Introductionmentioning
confidence: 99%
“…After mothers have experienced NICU hospitalization of their baby, there are a number of factors that infl uence future decisions about having subsequent children. These include fear of: becoming ill, giving birth to a premature baby, the fi rst child demanding its full attention, hospital admission (Funaba, Yokoo, & Fukuhara, 2011;Schaaf et al, 2011), a stressful experience in the NICU, and childbirth (Funaba et al, 2011). These reasons differ from more common reasons of mothers in general when they are deciding whether or not to have a child, such as the importance to the couple of having another child, and fi nancial and medical reasons (Brien & Fairbairn, 1996).…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…In previous studies, mothers abandoned plans for subsequent pregnancies because of anxiety and fear of having the same complications of pregnancy, anxiety and fear of admission to the NICU, and because of the burden of bringing up a child who had been hospitalized in the NICU (Funaba et al, 2011;Schaaf et al, 2011). Our study found a similar result, such as hesitating to repeat the stressful experience of hospitalization in the NICU, and anxiety and fear that a subsequent child would have a painful experience in the NICU.…”
Section: Clinical Nursing Implicationsmentioning
confidence: 99%